(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Syntaxonomical research of the coastal vegetation of Ukraine on basis of the Braun- Blanquet method is summarized. Some questions are elucidated and some questions for future research are figured out.